2018 IEEE 23rd International Workshop on Computer Aided Modeling and Design of Communication Links and Networks (CAMAD) 2018
DOI: 10.1109/camad.2018.8514972
|View full text |Cite
|
Sign up to set email alerts
|

Optical and wireless network convergence in 5G systems – an experimental approach

Abstract: This paper provides a description of key results stemming from experiments conducted at the wireless/optical boundary. The main aim is to show the advantages of a converged optical/wireless network deployment, which uses very recent technologies like SDN, Virtualization, fog and cloud computing, and Radio-over fiber. The results are mainly taken out of an international collaborative research project called FUTEBOL (Federated Union of Telecommunications Research Facilities for an EU Brazil Open Laboratory).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…They observed that the 5G operation of the robots was superior in terms of control-loop reliability to the one of Wi-Fi 6 and the potential of 5G for reliably operating autonomous mobile robots. Marques et al [2018] analysed and presented the impact of software-defined networks and cloud computing technologies in systems running real-time applications with low end-to-end latency and high bandwidth requirements. Thus, to achieve URLLC in wireless networks to support robot mobility, they proposed and implemented a splitting of the WiFi architecture functionalities that provides multiconnectivity and redundant communication by offering seamless mobility and failover resilience.…”
Section: Related Workmentioning
confidence: 99%
“…They observed that the 5G operation of the robots was superior in terms of control-loop reliability to the one of Wi-Fi 6 and the potential of 5G for reliably operating autonomous mobile robots. Marques et al [2018] analysed and presented the impact of software-defined networks and cloud computing technologies in systems running real-time applications with low end-to-end latency and high bandwidth requirements. Thus, to achieve URLLC in wireless networks to support robot mobility, they proposed and implemented a splitting of the WiFi architecture functionalities that provides multiconnectivity and redundant communication by offering seamless mobility and failover resilience.…”
Section: Related Workmentioning
confidence: 99%